Migration of female Prostitutes in Brothels, Muang District, Ratchaburi - Sankamanee, Thawin; Sangpudsa, Arun (Journal of Health Science of Thailand, 1994)
The study emphazied on the migration of female prostitutes in brothels in Muang District, Ratchaburi, who had came to receive medical services from the Venereal Disease Control Centre, Region 4, Ratchaburi province, during the period from 1 October 1991 - 30 September 1992. There were 2,357 cases: 1,281 direct prostitutes (54.35%) and 1,076 indirect prostitutes (45.65%) It was found that migration was reported in 42.34% of the samples. The rate of migrating-in was 21.09% where as the rate of migrating—out was 21.26%. Direct prostitute group had migration around 40.12%. The rate of migrating-in was 26.45% and the rate of migrating—out was 19.67%, which was not significantly different. In indirect prostitute group, 44.98% of them reported migration. The rate of migrating-in was 21.48% and the rate of mi grating-out was 23.14% which was also not significantly different. It is revealed that the mi grating-in prostitutes were found to be more new cases (77.46%) than those old ones (22.54%), the difference was statistically significant.